ANALYSIS OF BUSINESS DEVELOPMENT STRATEGY AGROWISATA BENTENQ FARMHOUSE HIDROPONIK TASIKMALAYA CITY WITH BUSINESS MODEL CANVAS APPROACH - Cantika Dwi Destari, Tasya; Husyairi, Khoirul Aziz (PUSAT SAINS INDONESIA, 2022)
This study aims to analyze the business development strategy of Bentenq Farmhouse Hidroponik Agrotourism using the Business Model Canvas approach. The research method used is descriptive qualitative research. Data collection techniques used are in-depth interviews and literature studies. The analysis was carried out using the Business Model Canvas and SWOT analysis. The results obtained are Bentenq Farmhouse Hidroponik Agrotourism need to optimized online media as part of digital marketing to expand the market segment. Keyword : Benteng Farmhouse Hirodroponik, SWOT analysis, Business Model Canvas